Ranking Determinants of Students’ Choice in Selecting a University - Siti Rahayu Mohd. Hashim; Nielson Lorensius (Faculty of Science & Natural Resources, UMS, 2022)
There are many criteria that contribute to the final decision in selecting a university. It is crucial for any university to understand and identify the most important criteria that lead to the student's university selection. It will definitely help a university to plan and redevelop its promotional materials and approaches in order to increase the number of students enrolled at their respected university. This study aims to determine the determinant factors, identify the most important factors affecting university selection among students and compare the determinants’ ranking between groups. Factor analysis was conducted to determine the significant factors whereas Multiple Weighted-Score analysis (MWS) was used to rank the factors. There were 226 first year students from University Malaysia Sabah (UMS) participated in this study. An online survey was carried out using a self-developed instrument which consists of nine criteria or factors. Seven determinants were identified from the factor análysis which are Promotion, Reputation, Recommendation, Financial Reason, Friend Enrolled, Family Enrolled, Distance and Location. The result of the analysis found that Reputation, Distance and Location, Financial Reason and Recommendation are the top four determinants of the students’ choice in selecting a university. The rankings of the determinants are varies according to different programs under study.